The role of endoscopic ultrasonography in choledocholithiasis - Ülkü SARITAŞ; Bülent YILDIRIM; Uğur YILMAZ; Burhan ŞAHİN and Gülay TEMUÇİN and Gönül GÜRKAYNAK (Turkish Journal of Gastroenterology, 2020)
-